2007
DOI: 10.1029/2006jb004376
|View full text |Cite
|
Sign up to set email alerts
|

Effect of predeformational basin geometry in the kinematic evolution of a thin‐skinned orogenic wedge: Insights from three‐dimensional finite element modeling of the Provo salient, Sevier fold‐thrust belt, Utah

Abstract: [1] In fold-thrust belts, sedimentary cover rocks are detached from undeformed basement and undergo crustal-scale shortening and internal deformation. We have investigated a three-dimensional (3-D), nonlinear, elastic-plastic finite element model using the restored Provo salient of the Sevier belt as our initial configuration. In the model the deformed sedimentary prism displays large-scale geometries that are seen in many natural fold-thrust belts (e.g., arcuate salient, wedge-shaped cross section) and kinema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…This is consistent with the fact that Sh min orientations, differently from the general trend, here become parallel to the direction of regional shortening. Such a rotation is consistent also with what predicted by our 3‐DMIRA model after the slip of the fault and is in line with the results of 3‐D numerical models dedicated to other regions, showing that lateral variations in the geometry of active structures control the present‐day state of stress [ Hu et al , 1997; Kwon et al , 2007].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This is consistent with the fact that Sh min orientations, differently from the general trend, here become parallel to the direction of regional shortening. Such a rotation is consistent also with what predicted by our 3‐DMIRA model after the slip of the fault and is in line with the results of 3‐D numerical models dedicated to other regions, showing that lateral variations in the geometry of active structures control the present‐day state of stress [ Hu et al , 1997; Kwon et al , 2007].…”
Section: Discussionsupporting
confidence: 89%
“…The geomechanical properties (Tables 2 and 3 assumed for each formation in the 2‐D models (Young's modulus, Poisson's ratio, density) were obtained from sonic compressional and shear, and bulk density logs [ Biot and Willis , 1957; Harrison et al , 1990] applying also the correction from dynamic to static Young's modulus and are consistent with values commonly used in the literature [e.g., Zhao et al , 2004; Chamlagain and Hayashi , 2007; Kwon et al , 2007]. Several simulations, not shown, were done varying the elatic parameters but no significant changes were obtained in the predicted stress field.…”
Section: Model Descriptionmentioning
confidence: 91%
“…Therefore, the strain ellipsoids are affected by the N‐S trending antiform, and the Y ‐axis exhibits the strongest lateral variation as compared to the X‐ and the Z ‐axes. Previous studies from various FTBs have shown that lateral variations in thrust sheet geometry at the regional scale, as manifested by salient‐recess pairs, can affect the strain ellipsoid geometry (e.g., Kwon & Mitra, 2004; Kwon et al., 2007; Mitra, 1997; Strine & Mitra, 2004). This study shows that even smaller scale lateral variation in the thrust geometry (∼15 km) can also affect and modify strain ellipsoid geometry of thrusts.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the structures of orogens vary laterally (e.g., Bhattacharyya & Ahmed, 2016; Macedo & Marshak, 1999; Mitra et al., 2010). Although there are studies addressing strain variation at a larger‐scale, for example, salient‐recess pairs (Kwon & Mitra, 2004; Kwon et al., 2007; Law et al., 2010; Mitra, 1997; Strine & Mitra, 2004), effects of smaller‐scale along‐strike structural variation in thrusts on strain geometry and magnitude are not very well understood. Therefore, partitioning of convergence‐related shortening into major thrust sheets and penetrative strain within the corresponding thrust sheets, their spatial variations within the orogenic wedge, and contribution of penetrative strain into total shortening budget remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…A similar framework emerges also from a certain number of case histories in the Apennines and Sicily at various scales, especially from a geometric point of view, mainly based on 2D representations (cross-sections parallel to the tectonic transport direction: Tavarnelli et al 2004;Scisciani 2009 andDi Francesco et al 2010 for a review). Nevertheless, recently there has been growing attention towards 3D kinematic reconstructions of the evolution of non-cylindrical structures in fold-and-thrust belts through both numerical and analogue modelling (Corrado et al 1998;McClay et al 2004;Kwon et al 2007, and references therein).…”
Section: Introductionmentioning
confidence: 98%